Prevention of post-infarction cardiac remodeling after using the non-cellular biomaterial in the experiment - S. A. Afanasiev; D. S. Kondratyeva; V. Yu. Usov; A. I. Lebedeva; S. A. Muslimov; S. V. Popov (Российский кардиологический журнал, 2019)
Aim. To assess the effect of non-cellular allogenic material (NAM) on post-infarction myocardial remodeling in the experiment.Material and methods. We ligated left descending coronary artery of control Han Wistar rats in order to simulate post-infarction cardiosclerosis (PICS), and NAM was intramyocardially administered to the experimental animals at the same time as the coronary occlusion. The formation of PICS occurred within 45 days after myocardial infarction modeling. Exercise tolerance was assessed in rats before and after exposure. Magnetic resonance imaging (MRI) of the rat heart was performed on 7th, 14th, and 45th days after myocardial infarction modeling. Postinfarction remodeling of rat heart was assessed using morphometric research methods.Results. An MRI study showed that on 7th day hearts of the rats of both groups had areas of damaged myocardium. However, on 14th day the area of damaged myocardium in rats with injection of NAM was 2 times less than in individuals with PICS, and on 45 day this difference increased 3,5 times. The increase in end-diastolic volume (EDV) of the left ventricle of control animals on 45 day amounted to 30%, whereas in rats of the experimental group, this figure was 8% of the initial values. Exercise tolerance in rats of both groups after the formation of PICS was lower than in the initial state. At the same time, in animals with injection of NAM, resistance to exercise was significantly higher than in rats of the control group. The results of morphometric studies of the heart showed that in the control group there were significantly more animals with morphologically visible infarction and left ventricular aneurysm than in the experimental group. In addition, animals of the control group were characterized by a statistically significantly higher value of heart mass/body weight ratio.Conclusion. Based on the results obtained, it can be considered that intramyocardial injections of non-cellular allogenic biomaterial manufactured according to the Alloplant® technology create conditions for stimulating the regenerative processes in the myocardium and also prevent post-infarction heart remodeling.